− K x → ∞ lim x − 3 9 x 2 − 1 − x = y → − ∞ lim y − 3 9 y 2 − 1 − y
Given that constant K satisfy the equation above, find K .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The first limit is equal to 2, not -2.
Log in to reply
Thank you for spotting my mistake. I've made the necessary changes.
Note that x → − ∞ lim x − 3 9 x 2 + 1 − x = x → ∞ lim − x − 3 9 x 2 + 1 + x Hence − K x → ∞ lim x − 3 9 x 2 + 1 − x = x → ∞ lim − x − 3 9 x 2 + 1 + x K = − lim x → ∞ x − 3 9 x 2 + 1 − x lim x → ∞ − x − 3 9 x 2 + 1 + x = x → ∞ lim 9 x 2 + 1 − x 9 x 2 + 1 + x ⋅ x → ∞ lim x + 3 x − 3 = x → ∞ lim 9 + x 2 1 − 1 9 + x 2 1 + 1 ⋅ x → ∞ lim 1 + x 3 1 − x 3 = 3 − 1 3 + 1 ⋅ 1 K = 2
Problem Loading...
Note Loading...
Set Loading...
For the limit on the LHS, we divide the numerator and the denominator by x , to get
x → ∞ lim ( x − 3 9 x 2 − 1 − x ÷ x x ) = = x → ∞ lim ⎝ ⎜ ⎜ ⎛ 1 − x 3 9 − x 2 1 − 1 ⎠ ⎟ ⎟ ⎞ 1 − 0 9 − 0 − 1 = 2
However, it gets trickier if x → − ∞ , because we're dealing with radical functions, let's try to apply a substitution of y = − x , so that we're only dealing with positive numbers. Thus when x → − ∞ , y → ∞ , and so the limit becomes y → ∞ lim − y − 3 9 y 2 − 1 + y
Likewise, we divide the numerator and the denominator by y , to get
y → ∞ lim ( − y − 3 9 y 2 − 1 + y ÷ y y ) = = y → ∞ lim ⎝ ⎜ ⎜ ⎛ − 1 − y 3 9 − y 2 1 + 1 ⎠ ⎟ ⎟ ⎞ − 1 − 0 9 − 0 + 1 = − 4
Putting this all together, we have ( − K ) ( − 2 ) = − 4 ⇒ K = 2 .